2013
DOI: 10.4047/jap.2013.5.4.416
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of MC3T3-E1 osteoblastic cells on titanium and zirconia surface

Abstract: PURPOSEThis study was performed to define attachment and growth behavior of osteoblast-like cells and evaluate the gene expression on zirconia compared to titanium.MATERIALS AND METHODSMC3T3-E1 cells were cultured on (1) titanium and (2) zirconia discs. The tetrazolium-based colorimetric assay (MTT test) was used for examining the attachment of cells. Cellular morphology was examined by scanning electron microscopy (SEM) and alkaline phosphatase (ALP) activity was measured to evaluate the cell differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…When the MTF was modified with hrBMP‐2 (Figure S4, Supporting Information), the cell shape was more elongated if compared with cells cultured 48 h on the bare MTFs (Figure S5, Supporting Information) or hrBMP‐2 and gentamicin (Figure ). This cell shape and higher filopodia means cells were interacting better when hrBMP‐2 was present on the surface and were well attached. This does not mean that cell attachment was not good on the other substrates, on which focal adhesion points and a well‐arranged cytoskeleton were as well present.…”
Section: Resultsmentioning
confidence: 99%
“…When the MTF was modified with hrBMP‐2 (Figure S4, Supporting Information), the cell shape was more elongated if compared with cells cultured 48 h on the bare MTFs (Figure S5, Supporting Information) or hrBMP‐2 and gentamicin (Figure ). This cell shape and higher filopodia means cells were interacting better when hrBMP‐2 was present on the surface and were well attached. This does not mean that cell attachment was not good on the other substrates, on which focal adhesion points and a well‐arranged cytoskeleton were as well present.…”
Section: Resultsmentioning
confidence: 99%
“…Zirconia showed comparable biological responses of osteoblast-like cells to titanium for a short time during the cell culture period. Most genes related to cell adhesion and signal showed a similar expression level between titanium and zirconia 102) . No significant 93) This review started with a PubMed search from 1975 to 2009.…”
Section: Bone Formation and Bone Bondingmentioning
confidence: 86%
“…Osteoblasts-like cell adhesion in monoculture has been found to be enhanced on ZrO 2 compared to pure Ti and also the gene expression of integrin β1, ERK1/2 and c-fos was higher on ZrO 2 than on Ti, 44 although other monoculture studies showed no difference in initial cell response to Ti and ZrO 2 . 45,46 Previous work 11 employing an aerobic, peri-operative, co-culture model consisting of human gingival fibroblasts and supra-gingival oral bacteria, pointed out that a soft tissue seal as needed on the neck part of an implant, develops more readily on bacterially contaminated, smooth Ti surfaces (see also Figure 7, right panels). Therewith our previous 11 and present co-culture studies on dental implant materials indicate that different requirements should be set to the materials properties for the neck versus the osseointegratable part of a dental implant.…”
Section: Discussionmentioning
confidence: 99%